Experiential Education and Adolescents’ Personal and Spiritual Development - Cheung, Chung Kwan Ackie. author. aut Link
206 p.
Keywords: Adventure-based programs have become prevailing in the schools in Hong Kong. Due to the little empirical examination to the frequent use of experiential education, Chung Kwan Ackie Cheung uses mixed methods to establish its first phenomenal picture, addressing the scale of the use of experiential education and the impact of it on adolescents’ development with regard to the globalizing phenomenon of Hong Kong. The findings show that experiential education, esp. adventure-based program, has been widely-spread and there is positive impact in the specified aspects self-concept, self-efficacy, learning climate and spiritual dimension of its adolescent learners.